The sensitivity of donor – acceptor charge transfer to molecular geometry in DAN – NDI based supramolecular flower-like self-assemblies. Issue 1 (December 2017) - Kobaisi, Mohammad; Bhosale, Rajesh; El-Khouly, Mohamed; La, Duong; Padghan, Sachin; Bhosale, Sidhanath; Jones, Lathe; Antolasic, Frank; Fukuzumi, Shunichi; Bhosale, Sheshanath
Abstract A charge-transfer (CT) complex self-assembled from an electron acceptor (NDI-EA: naphthalene diimide with appended diamine) and an electron donor (DAN: phosphonic acid-appended dialkoxynapthalene) in aqueous medium. The aromatic core of the NDI and the structure of DAN1 were designed to optimize the dispersive interactions (π-π and van der Waals interactions) in the DAN1–NDI-EA self-assembly, while the amino groups of NDI also interact with the phosphonic acid of DAN1 via electrostatic forces. This arrangement prevented crystallization and favored the directional growth of 3D flower nanostructures. This molecular geometry that is necessary for charge transfer to occur was further evidenced by using a mismatching DAN2 structure. The flower-shaped assembly was visualized by scanning electron and transmission electron microscopy. The formation of the CT complex was determined by UV-vis and cyclic voltammetry and the photoinduced electron transfer to produce the radical ion pair was examined by femtosecond laser transient absorption spectroscopic measurements.